Facile Construction of Porous ZnMn2O4 Hollow Micro-Rods as Advanced Anode Material for Lithium Ion Batteries - Yuyan Wang; Senyang Xu; Yamin Zhang; Linrui Hou; Changzhou Yuan (Nanomaterials, 2023)
Spinel ZnMn2O4 is considered a promising anode material for high-capacity Li-ion batteries due to their higher theoretical capacity than commercial graphite anode. However, the insufficient cycling and rate properties seriously limit its practical application. In this work, porous ZnMn2O4 hollow micro-rods (ZMO HMRs) are synthesized by a facile co-precipitation method coupled with annealing treatment. On the basis of electrochemical analyses, the as-obtained samples are first characterized by X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy, and scanning electron microscopy techniques. The influences of different polyethylene glycol 400 (PEG 400) additions on the formation of the hollow rod structure are also discussed. The abundant multi-level pore structure and hollow feature of ZMO HMRs effectively alleviate the volume expansion issue, rendering abundant electroactive sites and thereby guaranteeing convenient Li+ diffusion. Thanks to these striking merits, the ZMO HMRs anode exhibits excellent electrochemical lithium storage performance with a reversible specific capacity of 761 mAh g−1 at a current density of 0.1 A g−1, and a long-cycle specific capacity of 529 mAh g−1 after 1000 cycles at 2.0 A g−1 and keep a remarkable rate capability. In addition, the assembled ZMO HMRs-based full cells deliver an excellent rate capacity, and when the current density returns to 0.05 A g−1, the specific capacity can still reach 105 mAh g−1 and remains at 101 mAh g−1 after 70 cycles, maintaining a material-level energy density of approximately 273 Wh kg−1. More significantly, such striking electrochemical performance highlights that porous ZMO HMRs could be a promising anode candidate material for LIBs.